Minimax filtration of linear transformations of stationary consequences - Moklyachuk , M. P. (Ukrains’kyi Matematychnyi Zhurnal, 1991)
We will consider the problem of determining a linear, mean-square optimal estimate of the transformation Aξ = _j=0^∞a(j)ξ(-j) of a stationary random sequence ξ(k) with density f (λ) from observations of the sequence ξ(k)+η(k) with k≤ 0, where η(k) is a stationary sequence not correlated with ξ (k) with density g(λ). The least favorable spectral densities f_0(λ)D_f, g_0(λ)D_g, and minimax (robust) spectral characteristics of an optimal estimate Aξ for different classes of densities D_f, D_g.